Love is a pain? Quality of sex life after surgical resection of endometriosis: a review. (February 2017) - Fritzer, N.; Hudelist, G.
Abstract: Dyspareunia, a common symptom of endometriosis and may severely affect quality of sex life in affected patients. The objective of the present work was to review the effect of surgical resection of endometriosis on pain intensity and quality of sex life. MEDLINE and EMBASE databases were searched for papers investigating the outcome after surgical endometriosis resection on dyspareunia and quality of sex life measured via VAS/NAS respectively via standardized measuring instruments. However, data did not permit a meaningful meta-analysis according to current standards. However, out of 69 papers, four studies fulfilled the predefined inclusion criteria involving 321 patients with endometriosis and dyspareunia preoperatively. All included studies showed a significant postoperative reduction of dyspareunia after a follow-up period of 10 up to 60 months. Sex life as well as predominantly evaluated parameters like quality of life and mental health improved significantly. We therefore conclude that surgical excision of endometriosis is a feasible and good treatment option for pain relief and improvement of quality of sex life in symptomatic women with endometriosis.